Gametocidal genes: from a discovery to the application in wheat breeding - Said, Mahmoud; Gaál, Eszter; Farkas, András; Molnár, István; Bartoš, Jan; Doležel, Jaroslav; Cabrera, Adoración; Endo, Takashi R. (Frontiers in Plant Science, 2024)
Some species of the genus Aegilops, a wild relative of wheat, carry chromosomes which after introducing to wheat exhibit preferential transmission to progeny. Their selective retention is a result of the abortion of gametes lacking them due to induced chromosomal aberrations. These chromosomes are termed Gametocidal (Gc) and based on their effects, they are categorized into three types; mild, intense or severe, and very strong. Gc elements within the same homoeologous chromosome groups of Aegilops (II, III, or IV) demonstrate similar Gc action. This review explores the intriguing dynamics of Gc chromosomes and encompasses comprehensive insights into their source species, behavioral aspects, mode of action, interactions, suppressions, and practical applications of the Gc system in wheat breeding. By delving into these areas, this work aims to contribute to the development of novel plant genetic resources for wheat breeding. The insights provided herein shed light on the utilization of Gc chromosomes to produce chromosomal rearrangements in wheat and its wild relatives, thereby facilitating the generation of chromosome deletions, translocations, and telosomic lines. The Gc approach has significantly advanced various aspects of wheat genetics, including the introgression of novel genes and alleles, molecular markers and gene mapping, and the exploration of homoeologous relationships within Triticeae species. The mystery lies in why gametes possessing Gc genes maintain their normality while those lacking Gc genes suffer abnormalities, highlighting an unresolved research gap necessitating deeper investigation.